2017
DOI: 10.1055/s-0043-122077
|View full text |Cite
|
Sign up to set email alerts
|

Is Venlafaxine More Effective than Escitalopram and Nortriptyline in the Management of Painful Symptoms in Patients with Major Depression?

Abstract: Our results do not support the hypothesis suggesting the superiority of VEN over ESC and NOR in the management of UPPS in major depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“… 19 From the perspective of pharmacology, the switch to a different mechanism of antidepressants would contribute to affecting different signs and symptoms. 20 , 21 This variation strategy may provide more chances of cure 22 when comparing the effects of sertraline with duloxetine, 23 rather than those of venlafaxine with escitalopram. 22 In the first-line recommendations, the prescription of bupropion was surprisingly low, even lower than the second-line recommendations except for quetiapine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 19 From the perspective of pharmacology, the switch to a different mechanism of antidepressants would contribute to affecting different signs and symptoms. 20 , 21 This variation strategy may provide more chances of cure 22 when comparing the effects of sertraline with duloxetine, 23 rather than those of venlafaxine with escitalopram. 22 In the first-line recommendations, the prescription of bupropion was surprisingly low, even lower than the second-line recommendations except for quetiapine.…”
Section: Discussionmentioning
confidence: 99%
“… 20 , 21 This variation strategy may provide more chances of cure 22 when comparing the effects of sertraline with duloxetine, 23 rather than those of venlafaxine with escitalopram. 22 In the first-line recommendations, the prescription of bupropion was surprisingly low, even lower than the second-line recommendations except for quetiapine. Efforts remain to be made to promote the coverage of bupropion in China from the aspects of efficiency and security.…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine dysfunction is associated with depression [ 35 ] and increased pain sensitivity in several chronic pain conditions [ 36 , 37 ]. Clinical practice has shown that some selective serotonin reuptake inhibitors (SSRIs) [ 38 ], serotonin norepinephrine reuptake inhibitors (SNRI) [ 29 ], and norepinephrine reuptake inhibitors (NRIs) [ 39 ] showed good efficacy in the control of both depression and pain. Raphe nucleus is abundant of serotonergic neurons [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, studies by Jaracz et al [65] indicate the similar efficacy of SNRI and SSRI in relieving unexplained painful physical symptoms associated with depression. In patients with severe depression, comparable analgesic efficacy has been demonstrated for venlafaxine, escitalopram, and nortriptyline [66]. From the SNRI group, venlafaxine and duloxetine are often used in practice.…”
Section: Treatment Of Depressionmentioning
confidence: 99%